KEBIJAKAN PEMERINTAH KABUPATEN KUANTAN SINGINGI DALAM PENGENDALIAN KERUSAKAN LINGKUNGAN HIDUP AKIBAT PERTAMBANGAN EMAS TANPA IZIN (PETI) TAHUN 2013-2015 - Putra, Mido; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Unauthorized Gold Mining (PETI) activities that occur in Kuantan Singingi is still ongoing and need special handling from government. PETI control policy has taken by Kuantan Singingi District's government through a Regent Decree No. 13 of 2013 About Formation of a Team of Integrated Control of Unauthorized Gold Mining (PETI) as a rescue of environmental damage efforts and social and economic life of society repair in the future.This research was conducted at the Department of Energy and Mineral Resources and the Environment Agency Kuantan Singingi District. This research method was qualitative research. Data collection techniques used were documentation, interviews and observation. While the data analysis performed descriptively. This study examines the implementation of PETI's control policies and the effectiveness of environmental damage control policies implementation damage caused by PETI well as the factors that influence Kuantan Singingi District's Government policy implementation in the control of environmental damage due to PETI.The study results showed that the control of environmental damage due to PETI policies implementation in Kuantan Singingi year 2013-2015 not implemented effectively and well, proven by today still ongoing PETI activities that cause a lot of environmental damage without decisive action from the government due to various constraints and inadequate supporting factors in the field.Keywords : Unauthorized Gold Mining (PETI), Government’s Policies, Environmental Damage Caused.